2018
DOI: 10.1016/j.ibror.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Glioblastoma in Moroccan population: Review of literature

Abstract: Glioblastoma is the most aggressive malignant type of central nervous system tumors. The literature review revealed that the most common genetic abnormalities in primary and secondary glioblastomas are IDH1 / 2 mutations, p53 mutations, and overexpression of EGFR.To our knowledge, this is the first Moroccan study to provide a global picture of genetic studies performed on Moroccan patients to describe genetic markers and their frequency in our population.An in-depth research in ScienceDirect and Pubmed on glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…No similar studies were found in North Africa. For instance, a Moroccan study summarized 3 research works with 65, 62 and 34 patients, on the frequency of altered genes in patients with glioblastoma, where only alteration of IDH1/2, p53 and EGFR expression were analysed [27]. The frequency of these gene mutation in Moroccan population was similar to those reported from other populations.…”
Section: Discussionmentioning
confidence: 61%
“…No similar studies were found in North Africa. For instance, a Moroccan study summarized 3 research works with 65, 62 and 34 patients, on the frequency of altered genes in patients with glioblastoma, where only alteration of IDH1/2, p53 and EGFR expression were analysed [27]. The frequency of these gene mutation in Moroccan population was similar to those reported from other populations.…”
Section: Discussionmentioning
confidence: 61%